2021
DOI: 10.3389/feart.2021.639692
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Attenuation Tomography From 2018 Lombok Earthquakes, Indonesia

Abstract: Local earthquake data was used to determine a three-dimensional (3D) seismic attenuation structure around the aftershock source region of the 2018 Lombok earthquake in Indonesia. The aftershocks were recorded by 13 seismic stations from August 4 to September 9, 2018. The selected data consist of 6,281 P-wave t∗ values from 914 events, which had good t∗ quality in at least four stations. Our results show that the two aftershock clusters northwest and northeast of Lombok Island have different attenuation charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 56 publications
0
4
0
1
Order By: Relevance
“…Sasmi et al (2020) explained that the 2018 Lombok earthquake aftershocks were mostly distributed to the depth of < 20 km with an average hypocenter slope of ~30 o and thought to be related with the rupture zone of 2018 Lombok earthquake. These significant events of earthquake were suspected as a result of the oceanic crust slabbed to the north of Lombok Islands and caused fault segmentation (Sasmi et al, 2020;Afif et al, 2021;Priyono et al, 2021;Wang et al, 2020;Salman et al, 2020;Yang et al, 2020;Lythgoe et al, 2021). The results from these studies confirm that the lack of correlation between event depths and δt suggests the shallow anisotropic fabrics may control the main possible sources of anisotropy in this area.…”
Section: The Influence Of Structure Induced Anisotropymentioning
confidence: 59%
See 2 more Smart Citations
“…Sasmi et al (2020) explained that the 2018 Lombok earthquake aftershocks were mostly distributed to the depth of < 20 km with an average hypocenter slope of ~30 o and thought to be related with the rupture zone of 2018 Lombok earthquake. These significant events of earthquake were suspected as a result of the oceanic crust slabbed to the north of Lombok Islands and caused fault segmentation (Sasmi et al, 2020;Afif et al, 2021;Priyono et al, 2021;Wang et al, 2020;Salman et al, 2020;Yang et al, 2020;Lythgoe et al, 2021). The results from these studies confirm that the lack of correlation between event depths and δt suggests the shallow anisotropic fabrics may control the main possible sources of anisotropy in this area.…”
Section: The Influence Of Structure Induced Anisotropymentioning
confidence: 59%
“…This may be related to the influence of the crack zone formed during the 2018 Lombok significant earthquake (Sasmi et al, 2020;Afif et al, 2021;Priyono et al, 2021;Wang et al, 2020;Salman et al, 2020). Sasmi et al (2020) explained that the 2018 Lombok earthquake aftershocks were mostly distributed to the depth of < 20 km with an average hypocenter slope of ~30 o and thought to be related with the rupture zone of 2018 Lombok earthquake.…”
Section: The Influence Of Structure Induced Anisotropymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the difference is in the structure's location, which is in Lombok's northern region (Widyarta et al, 2020). Another tomographic study by Afif et al (2021) and Priyono et al (2021) found that aftershocks formed an east-west cluster due to the low seismic velocities of the local medium. High temperature, fluid, and numerous fractures are indicated by this.…”
Section: Resultsmentioning
confidence: 99%
“…Persamaan dari perhitungan kecepatan rupture gempa menggunakan Persamaan (2). (Priyono et al, 2021;Supendi et al, 2020). Hal ini didukung pula bahwa sejak 2005 pulau Lombok meningkat aktivitas seismik atau seismisitasnya khususnya di daerah back arc thrust di bagian Utara wilayah Lombok dibandingkan zona subduksi Lempeng Indo-Australia dengan Lempeng Eurasia bagian Selatan (Zubaidah et al, 2014).…”
Section: Teknik Pengolahan Dataunclassified